Multifunctional Nanoplatforms as a Novel Effective Approach in Photodynamic Therapy and Chemotherapy, to Overcome Multidrug Resistance in Cancer - Martin Majerník; Rastislav Jendželovský; Jana Vargová; Zuzana Jendželovská; Peter Fedoročko (MDPI AG, 2022)
It is more than sixty years since the era of modern photodynamic therapy (PDT) for cancer began. Enhanced selectivity for malignant cells with a reduced selectivity for non-malignant cells and good biocompatibility along with the limited occurrence of side effects are considered to be the most significant advantages of PDT in comparison with conventional therapeutic approaches, e.g., chemotherapy. The phenomenon of multidrug resistance, which is associated with drug efflux transporters, was originally identified in relation to the application of chemotherapy. Unfortunately, over the last thirty years, numerous papers have shown that many photosensitizers are the substrates of efflux transporters, significantly restricting the effectiveness of PDT. The concept of a dynamic nanoplatform offers a possible solution to minimize the multidrug resistance effect in cells affected by PDT. Indeed, recent findings have shown that the utilization of nanoparticles could significantly enhance the therapeutic efficacy of PDT. Additionally, multifunctional nanoplatforms could induce the synergistic effect of combined treatment regimens, such as PDT with chemotherapy. Moreover, the surface modifications that are associated with nanoparticle functionalization significantly improve the target potential of PDT or chemo-PDT in multidrug resistant and cancer stem cells.